Bilateral corneal perforation following the use of traditional herbal medicine treated with conjunctival flap - Naviri, Varanisese; Dethlefs, Roger (Nepalese Journal of Ophthalmology, 2014)
Introduction: The harmful effect of the herbal medicine to the eye has not been well reported in the literature.Objective: To report a case of bilateral corneal perforation following the use of traditional herbal medicine treated with conjunctival flap.Case: A 46-year-old Fijian man initially presented with bilateral conjunctivitis, which was thought to be an allergic response to the use of herbal medicine. Vision at initial presentation was normal and he was treated conservatively. Upon review a week later, his vision had decreased to light perception in both eyes. The examination revealed bilateral corneal perforation with iris prolapse, which was then treated with a full thickness conjunctival flap in both eyes in the same sitting. Upon review at 3 weeks of intervention, his vision had improved to hand motions in the right eye and 6/60 in the left. The anterior chamber was formed on both sides.  Conclusion: This case illustrates that the use of herbal medicine can cause corneal melting and subsequently perforations and this can be treated with a conjunctival flap.DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11716Nepal J Ophthalmol 2014; 6(12): 237-239